Continuous carbon fiber/crosslinkable poly(ether ether ketone) laminated composites with outstanding mechanical properties, robust solvent resistance and excellent thermal stability. (8th September 2018) - Zhang, Yunhe; Tao, Wei; Zhang, Yu; Tang, Lin; Gu, Junwei; Jiang, Zhenhua
Abstract: Continuous carbon fiber (CCF) reinforced polymeric composites have attracted significant attention in the aeronautic and automobile industries. In this study, novel CCF/poly(ether ether ketone) (PEEK) composites with robust solvent resistance, excellent thermal stability and outstanding mechanical properties were successfully fabricated via a facile solution impregnation process, mainly ascribed to the introduction of the crosslinkable phenylethynyl pendant to PEEK (PEP-PEEK) with excellent solubility. After the crosslinking reaction, PEP-PEEK presented robust solvent resistance, good thermal stability, and high mechanical properties. The longitudinal tensile strength of the CCF/PEP-PEEK composites significantly improved to 1610 MPa, which was 19 times stronger than the longitudinal tensile strength of PEP-PEEK. In the meantime, the CCF/PEP-PEEK composites also had a higher long-term operating temperature, excellent thermal stability and high heat distortion temperature. This study was performed as part of a larger effort to provide a simple and feasible method for the preparation of high quality continuous fiber reinforced poly(ether ether ketone) composites.